A geographic cline in the ability to self‐fertilize is unrelated to the pollination environment. Issue 11 (11th October 2017) - Koski, Matthew H.; Grossenbacher, Dena L.; Busch, Jeremiah W.; Galloway, Laura F.
Abstract: The reproductive assurance (RA) hypothesis predicts that the ability to autonomously self‐fertilize should be favored in environments where a lack of mates or pollinators limits outcross reproduction. Because such limits to outcrossing are predicted to be most severe at range edges, elevated autonomy in peripheral populations is often attributed to RA. We test this hypothesis in 24 populations spanning the range of Campanula americana, including sampling at the range interior and three geographic range edges. We scored autonomous fruit set in a pollinator‐free environment and detected clinal variation—autonomy increased linearly from the southern to the northern edge, and from the eastern to the western edge. We then address whether the cline reflects the contemporary pollination environment. We measured population size, plant density, pollinator visitation, outcross pollen limitation and RA in natural populations over two years. Most populations were pollen limited, and those that experienced higher visitation rates by bumblebees had reduced pollen limitation. Reproductive assurance, however, was generally low across populations and was unrelated to pollen limitation or autonomy. Neither pollen limitation nor RA displayed geographic clines. Finally, autonomy was not associated with pollinator visitation rates or mate availability. Thus, the data do not support the RA hypothesis; clinal variation in autonomy is unrelated to the current pollination environment. Therefore, geographic patterns of autonomy are likely the result of historical processes rather than contemporary natural selection for RA.